2014
DOI: 10.1080/03601277.2014.970419
|View full text |Cite
|
Sign up to set email alerts
|

“Why Give Up Something That Works So Well?”: Retirement Expectations Among Academic Physicians

Abstract: For individuals with strong work identities, the decision to retire can be particularly challenging. For academic physicians, retirement is an important personal decision that also has far-reaching implications for the healthcare system. This is because academic physicians are responsible for producing the research from which key medical decisions are made, for training future healthcare providers, and for providing specialized care for patients. For this study, we conducted focus groups with academic physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Qualitative studies [9, 18, 22–29] were found to be methodologically strong, with credible results deemed relevant to practice. The majority of quantitative studies had adequate sample representativeness (76% of studies), had justified and satisfactory sample size (89% of studies), used appropriate statistical tests (59% of studies), and collected primary data by self-reported survey methods (91% of studies).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies [9, 18, 22–29] were found to be methodologically strong, with credible results deemed relevant to practice. The majority of quantitative studies had adequate sample representativeness (76% of studies), had justified and satisfactory sample size (89% of studies), used appropriate statistical tests (59% of studies), and collected primary data by self-reported survey methods (91% of studies).…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should account for multiple interrelating factors such as gender, changes over time, and spousal retirement to further enhance our understanding of physicians' adjustment to retirement. [13][14][15][16]. Understanding the needs of physicians and factors that support their successful adjustment to late career transitions is a critical area for study.…”
Section: Discussionmentioning
confidence: 99%
“…Financial issues contributing to a physician's early retirement included: increasing costs of retaining a practice, malpractice costs and other economic pressures, [15,39,43,45,53] insufficient financial remuneration and, pension security [42,50,54,55]. Several studies noted that physicians working in institutions or in countries where the policy landscape changed considerably were more inclined to retire because of perceptions around doctoring regulations and poor work satisfaction as a result of circumstances arising from the delivery of care [19].…”
Section: Reasons For Retiring Earlymentioning
confidence: 99%
“…Physician retirement planning can create challenges when retirement or death inevitably occurs, because hospitals and medical institutions often find it difficult to replace experienced, older physicians and to facilitate knowledge transfer [17]. The career progression of a growing pool of younger physicians waiting in the wings for professional opportunities can also be impeded without individual physician and institutional hospital succession plans in place [18,19].…”
Section: Introductionmentioning
confidence: 99%